If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5s + -13 = -68 Reorder the terms: -13 + -5s = -68 Solving -13 + -5s = -68 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -5s = -68 + 13 Combine like terms: -13 + 13 = 0 0 + -5s = -68 + 13 -5s = -68 + 13 Combine like terms: -68 + 13 = -55 -5s = -55 Divide each side by '-5'. s = 11 Simplifying s = 11
| x-25=-9 | | -94x-76=-94-23x | | 4x=5+3.8*x | | 3(x+4)+1=31 | | 0.15(x+50)-0.04(x-20)=2.8 | | -6g+3(-7+4g)=1-g | | 2.5x+9=209+.5x | | 6w+48=48 | | -20=-4-(6x) | | y=-2/3(-1)+1 | | y=-2/3(1)+1 | | 2u=-8 | | z-0.5=0.25z-0.125 | | U-9.9=4.99 | | y=-2/3(0)+1 | | 9(4x+8)=12(12+3x) | | h=-16t^2+1000 | | 32=6(x+4)-8x | | (3x+4)+(2x+2)= | | 8+5(7+5n)=193 | | 2.5x+1.96=1.7x+2.92 | | w+6-13=-27 | | 3(5x+4)=31 | | 3x+2(5)=0.2(2y+1) | | 45+5.50x=195+4.25x | | -x+3(-x+8)=0 | | 3+4+a=12 | | (C+5)+(c-1)=90 | | 4y+6(y+8)= | | 3(x+1)+4x=24 | | 18.1--0.7=c | | 75c^2+90cd+27d^2= |